Neurotrophic Factor Levels in Preterm Infants: A Systematic Review and Meta-Analysis - Krey, Francieli Cristina; Stocchero, Bruna Alvim; Creutzberg, Kerstin Camile; Heberle, Bernardo Aguzzoli; Tractenberg, Saulo Gantes; Xiang, Li; Wei, Wei; Kluwe-Schiavon, Bruno; Viola, Thiago Wendt (Frontiers in Neurology, 2021)
Objectives: Through a systematic review and meta-analysis of the literature we aimed to compare the levels of BDNF, NGF, NT-3, NT-4 and GDNF between term and preterm infants, and investigate factors implicated in the variability of effect sizes estimates. Methods: The analysis was performed in three online databases, MEDLINE Complete, PsycINFO and CINAHL. A random effects model was used to calculate the standardized mean difference (SMD) of neurotrophic factor levels in preterm infants versus term within a 95% confidence interval (CI). To explore sources of heterogeneity meta-regression models were implemented. Results: Sixteen studies were included in this meta-analysis. A combined sample of 1379 preterm and 1286 term newborns were evaluated. We identified significant lower BDNF (SMD = -0.32; 95% CI: -0.59, -0.06; p = 0.014) and NT-3 (SMD = -0.31; 95% CI: -0.52, -0.09; p = 0.004) levels in preterm compared to term infants. No significant difference was observed in NGF and NT-4 levels between groups. Given that only two effect sizes were generated for GDNF levels, no meta-analytical model was performed. Meta-regression models revealed sample type (placental tissue, cerebrospinal fluid, peripheral blood, umbilical cord blood) as a significant moderator of heterogeneity for BDNF meta-analysis. No significant associations were found for gestational week, birth weight and clinical comorbidity of newborns with effect sizes. Conclusions: Our findings indicated that lower BDNF and NT-3 levels may be associated with preterm delivery. Future studies with larger samples sizes should investigate neurodevelopmental manifestations resulting from neurotrophic factors dysregulation among preterm infants.